1989
DOI: 10.1002/fld.1650090307
|View full text |Cite
|
Sign up to set email alerts
|

Robust semidirect finite difference methods for solving the Navier–Stokes and energy equations

Abstract: SUMMARYSemidirect solution techniques can be an effective alternative to the more conventional iterative approaches used in many finite difference methods. This paper summarizes several semidirect techniques which generally have not been applied to the Navier-Stokes and energy equations in finite difference form. The methods presented use both successive substitution and Jacobian-based updates as well as two variations of Broyden's full matrix update. A hybrid method is also presented, as is a norm-reducing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…As discussed by MacArthur and Patankar [4], since the segregated solver reduces the residual only locally a t each step of the solution process, its convergence rate is strongly influenced by the number of unknowns.…”
Section: Comparison Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed by MacArthur and Patankar [4], since the segregated solver reduces the residual only locally a t each step of the solution process, its convergence rate is strongly influenced by the number of unknowns.…”
Section: Comparison Of Resultsmentioning
confidence: 99%
“…However, segregated solvers sometimes cannot adequately handle strong coupling because of the approximations that produce the linearized systems. In addition, since the segregated solution approach reduces the residual only locally at each step, the number of iterations required for convergence and the computational effort tend to increase significantly as grids are refined (see, e.g., [4]). …”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear system is then linearized using Newton's method. It has been found that a fully coupled approach used with Newton's method can successfully achieve solutions that are not easily obtained using a sequential solver [9,11,121. An inexact Newton's method [13,141 employs an iterative solution technique to solve the linear system rather than a direct solver.…”
Section: Introductionmentioning
confidence: 98%
“…Primitive-variable formulations of incompressible Navier-Stokes fluid-flow problems are notoriously difficult to solve numerically. A robust technique is to use Newton iteration for the fully-coupled nonlinear equations [1,2,3,4,5,6,7,8,9,10]. This technique is commonly used at present since it requires few (if any) iteration parameters and converges more quickly than segregated approaches such as SIMPLE (Semi-Implicit Method for Pressure-Linked Equations) [11,12].…”
mentioning
confidence: 99%
“…A direct matrix method can be used to solve the Jacobian [1,2,4,6,7,8,9,10] but this is prohibitively expensive for three-dimensional problems. An alternative is to use an iterative matrix method.…”
mentioning
confidence: 99%